2021
DOI: 10.3390/plants10050983
|View full text |Cite
|
Sign up to set email alerts
|

‘Honeycrisp’ Bitter Pit Response to Rootstock and Region under Eastern New York Climatic Conditions

Abstract: There are still unknown factors at play in the causation of bitter pit in ‘Honeycrisp’ as well as in other apple varieties. To investigate some of these factors, we conducted a survey of 34 ‘Honeycrisp’ orchard blocks distributed across two disparate production regions in eastern New York State, representing a variety of rootstocks, over three growing seasons. Weather, soil, horticultural traits, fruit quality traits, pick timing, leaf and peel minerals were evaluated for their impact on bitter pit (BP) incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…The relation between fruit size and Ca-related physiological disorders is debatable, whereas many studies have shown a positive relation between BP and larger fruit size (Fallahi et al, 1985;Perring and Jackson, 1975;Reid and Kalcsits, 2020;Valverdi and Kalcsits, 2021), several others have not found a direct correlation (Amarante et al, 2020;Donahue et al, 2021;Ferguson and Watkins, 1992). Recently, Donahue et al (2021) suggested that the relation with fruit size and BP occurs only with exceptionally large fruit, in 'Honeycrisp' with 48 to 56 size box (equivalent to >89 mm fruit and 340 g fruit), below which threshold there is no correlation. Fruit load, in the current trial, had a strong negative correlation with GS incidence (y 5 À0.0078x 1 0.88, R 2 5 0.662, R 5 À0.814, P < 0.0001) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relation between fruit size and Ca-related physiological disorders is debatable, whereas many studies have shown a positive relation between BP and larger fruit size (Fallahi et al, 1985;Perring and Jackson, 1975;Reid and Kalcsits, 2020;Valverdi and Kalcsits, 2021), several others have not found a direct correlation (Amarante et al, 2020;Donahue et al, 2021;Ferguson and Watkins, 1992). Recently, Donahue et al (2021) suggested that the relation with fruit size and BP occurs only with exceptionally large fruit, in 'Honeycrisp' with 48 to 56 size box (equivalent to >89 mm fruit and 340 g fruit), below which threshold there is no correlation. Fruit load, in the current trial, had a strong negative correlation with GS incidence (y 5 À0.0078x 1 0.88, R 2 5 0.662, R 5 À0.814, P < 0.0001) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, in 2018, fruit size was 15% higher on 'M.9', which actually had reduced GS levels compared with 'G.41'. However, the role of fruit size has been debated as a factor associated with BP and other Carelated disorders (Donahue et al, 2021;Ferguson and Watkins, 1992). Crop load, on the other hand, has more widely been suggested as an important factor associated with Ca-related disorders and nutrient balance in apples (Ernani et al, 2008;Ferguson and Watkins, 1992;Robinson and Watkins, 2003;Serra et al, 2016;Volz et al, 1993).…”
Section: Nutrientsmentioning
confidence: 99%
“…Rootstocks can affect fruit nutrient composition and bitter pit susceptibility by affecting the nutrient absorption and distribution of trees (Fazio et al, 2020;Reig et al, 2018;Valverdi and Kalcsits, 2021). Donahue et al (2021) found no direct relationship between crop load and bitter pit incidence, and rootstock and climatic conditions were influential in the rate of bitter pit incidence.…”
Section: Yield Water Productivity Fruit Growth and Qualitymentioning
confidence: 99%
“…‘Honeycrisp’ is the third most-produced apple cultivar in the USA, after ‘Gala’ and ‘Red Delicious’ ( Donahue et al., 2021 ). The high market value and consumer demand for this variety is largely due to its unique fruit quality characteristics (juicy, crispy, and strong-flavored) and palatability at harvest, which are sustained during storage ( Al Shoffe et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Rootstock’s influence on BP was explained in light of rootstock differences in the absorption and transport of certain nutrients, which in turn affect the composition of the scion’s levels of K + , Mg 2+ and Ca 2+ . For instance, in a study conducted by Donahue et al., 2021 , the authors studied the effects of three rootstocks, M.9, M.26 and B.9 on BP incidence in ‘Honeycrisp’ apples and revealed that the peel Mg 2+ /Ca 2+ ratio and peel Ca 2+ level could be a good indicator of BP incidence. In a separate study, using a more genetically-diverse group of apple rootstocks, Fazio et al., 2020 , showed that rootstocks have a significant impact on the Ca 2+ , K + , and K + /Ca 2+ ratio in the scion tissues, and that K + /Ca 2+ in the leaves and fruit of the scion was tightly correlated with BP incidence.…”
Section: Introductionmentioning
confidence: 99%